Liability and Responsibility for Misuse of Digital Technology by Start-Up Companies in Legal Actions to the Public: Case Study of Toko Pedia Semarang Region - Irawan Malebra; Umar Farouk; Nur Rini; Paniya (Admisi dan Bisnis, 2025)
The advancement of digital technology has significantly transformed the economic sector, particularly through the emergence of e-commerce. However, behind these conveniences lies a legal challenge concerning the misuse of personal data by digital-based companies such as start-ups. This study aims to examine the legal liability and responsibility of start-up corporations in cases of digital technology misuse, with a case study focusing on the data breach involving Tokopedia users in the Semarang area. Employing a normative juridical approach, this research analyzes relevant legal frameworks, including the Law on Electronic Information and Transactions, Government Regulation No. 71 of 2019, and Law No. 27 of 2022 on Personal Data Protection. The findings indicate that Tokopedia, as an Electronic System Operator, has a legal obligation to safeguard user data and provide transparent notification in the event of a data breach. Tokopedia’s failure to protect the personal data of 91 million users constitutes a form of negligence that may be subject to legal sanctions. This study recommends both preventive and corrective measures for the government, particularly the Ministry of Communication and Informatics and the Central Java Communication Office, to strengthen regulations and oversight regarding personal data protection within the national digital ecosystem.   Kemajuan teknologi digital telah membawa transformasi signifikan dalam sektor ekonomi, khususnya melalui kehadiran e-commerce. Namun, di balik kemudahan tersebut, muncul persoalan hukum terkait penyalahgunaan data pribadi pengguna oleh perseroan berbasis digital seperti startup. Penelitian ini bertujuan untuk mengkaji aspek tanggung jawab hukum (liability and responsibility) perseroan start-up dalam penyalahgunaan teknologi digital, dengan studi kasus kebocoran data pribadi pengguna Tokopedia di wilayah Semarang. Penelitian menggunakan pendekatan yuridis normatif untuk menelaah peraturan perundang-undangan yang relevan, seperti Undang-Undang Informasi dan Transaksi Elektronik, Peraturan Pemerintah No. 71 Tahun 2019, dan Undang-Undang No. 27 Tahun 2022 tentang Perlindungan Data Pribadi. Hasil penelitian menunjukkan bahwa Tokopedia sebagai Penyelenggara Sistem Elektronik memiliki kewajiban hukum untuk menjaga keamanan data pengguna dan memberikan pemberitahuan secara transparan apabila terjadi pelanggaran. Kegagalan Tokopedia dalam melindungi 91 juta data pengguna merupakan bentuk kelalaian yang dapat dikenai sanksi hukum. Penelitian ini merekomendasikan langkah preventif dan korektif bagi pemerintah, khususnya Kementerian Komunikasi dan Informatika serta Dinas Kominfo Jawa Tengah, guna memperkuat regulasi dan pengawasan terhadap pelindungan data pribadi dalam ekosistem digital nasional.